An exploration of how broadly neutralizing antibodies might induce HIV remission: the 'vaccinal' effect. Issue 3 (18th May 2022) - Tipoe, Timothy; Fidler, Sarah; Frater, John
Abstract : Purpose of review: Broadly neutralizing antibodies (bNAbs) are a potential new therapeutic strategy to treat HIV infection. This review explores possible mechanisms of action of bNAbs and summarizes the current evidence supporting their immunomodulatory properties, which might lead to sustained virological remission – the 'vaccinal effect'. Recent findings: Antiretroviral therapy (ART) is required to confer lasting HIV suppression; stopping ART almost invariably leads to HIV recrudescence from a persistent pool of virally infected cells – the HIV reservoir. HIV-specific broadly neutralizing antibodies (bNAbs) may confer viral control after ART cessation predominantly through blockade of viral entry into uninfected target cells. In some human and animal studies, HIV bNAbs also conferred lasting viral suppression after therapeutic bNAb plasma levels had declined. Immune-modulatory mechanisms have been postulated to underlie this observation – the 'vaccinal effect'. Hypothesized mechanisms include the formation of immune complexes between bNAbs and HIV envelope protein, thereby enhancing antigen presentation and uptake by immune cells, with boosted adaptive immune responses subsequently controlling the HIV reservoir. Summary: There is emerging evidence for potent antiviral efficacy of bNAb therapy. Whether bNAbs can induce sustained viral suppression after dropping below therapeutic levels remains controversial. Mechanistic data from on-going and future clinical trials will help answer these questions.